Are periprosthetic osteolytic lesions in ankle worth bone grafting?. Issue 2 (June 2017) - Kohonen, Ia; Koivu, Helka; Tiusanen, Hannu; Kankare, Jussi; Vahlberg, Tero; Mattila, Kimmo
Highlights: Osteolysis continued to progress in majority (68%) of lesions around total ankle prostheses after bone grafting. In some bone grafted lesions (28%) the radiological survival remained excellent; i.e. no recurrent lesion appeared in the grafted area. Despite of progression of osteolysis, the possible upcoming arthrodesis may be technically easier due to better peri-implant bone stock achieved by previous grafting. Subjective function of ankle improved in majority (74%) of cases after bone grafting. Abstract: Background: We retrospectively evaluated the medium-term follow-up of bone grafting due to periprosthetic osteolytic lesions in ankles. Methods: 34 ankles (32 patients) with total ankle arthroplasty (TAA) underwent re operation. Indications were large periprosthetic osteolytic lesions or continuous growing of the lesions. The osteolytic lesions were imaged by CT before reoperation and once a year after that. The mean CT follow-up after re operation was 3.8 years (range, 2–6.2 years). Patient's clinical outcome was also monitored. Results: Osteolysis continued to progress in 44 bone grafted lesions (68%) in CT follow-up. Pain (p = 0.04) and location of the lesion (p = 0.03) were associated with progression of osteolysis. In 18 bone grafted osteolytic lesions (28%) the radiological survival remained excellent. 25 out of 34 ankles showed improvement of the function after bone grafting. Conclusions: There is no established treatment protocol for osteolysis around TAA. Bone grafting is one alternative in the treatment of osteolytic lesions.